2019
DOI: 10.1177/2394901519870888
|View full text |Cite
|
Sign up to set email alerts
|

Do Global Financial, Oil and Gold Volatility Shocks Affect the GCC Stock Markets?

Abstract: This study employed the non-structural VAR econometrics approach to examine the impact of Global Oil (OVX), Financial (VIX), and Gold (GVZ) volatility indices on GCC stock markets using a daily data set spanning from January 5, 2009 to August 16, 2018. From the VAR result obtained, disequilibrium in the global financial volatility (VIX) was able to significantly transmit negative shock to Bahrain and Kuwait stock markets and positive shock on GVZ. While the global Gold volatility was capable of transmitting fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A similar study was conducted on GCC countries to find out the degree of dependence between crude oil and equity markets (Mokni and Yousseff, 2019) and found there is a positive influence of crude prices on equity markets of GCC countries with a high degree of dependence on Saudi Arabia equity market. Ingalhalli et al (2016), Tursoy and Faisal (2017), Singh and Sharma (2018) and Alqahtani (2019) conducted studies considering the relationship between the stock market and more than two macroeconomic variables. Based on the discussion, since there is limited evidence of nexus between crude oil prices and Indian equity market; therefore, the study proposes to test the following hypothesis:…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…A similar study was conducted on GCC countries to find out the degree of dependence between crude oil and equity markets (Mokni and Yousseff, 2019) and found there is a positive influence of crude prices on equity markets of GCC countries with a high degree of dependence on Saudi Arabia equity market. Ingalhalli et al (2016), Tursoy and Faisal (2017), Singh and Sharma (2018) and Alqahtani (2019) conducted studies considering the relationship between the stock market and more than two macroeconomic variables. Based on the discussion, since there is limited evidence of nexus between crude oil prices and Indian equity market; therefore, the study proposes to test the following hypothesis:…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Bouri et al (2017) find evidence to support the presence of cointegration relationships and nonlinear causality amongst the oil, gold, and Indian stock markets. Alqahtani (2019) A review of the above studies raises the following crucially important questions: Does a stable relationship between currency and other markets exist? If so, what are the correct magnitude and sign of this linkage?…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Bouri et al [46] found evidence to support the presence of cointegration relationships and nonlinear causality amongst the oil, gold, and Indian stock markets. Alqahtani [47] found that global gold volatility can transmit positive shocks to the UAE stock market and that the OVX and VIX can influence the GCC stock markets. Dutta et al [48] identified the presence of cointegration between oil and precious metal prices and nonlinear causality between oil and gold markets.…”
Section: Review Of Related Literaturementioning
confidence: 99%